Patient‐specific simulation of guidewire deformation during transcatheter aortic valve implantation. (2nd April 2018) - Vy, Phuoc; Auffret, Vincent; Castro, Miguel; Badel, Pierre; Rochette, Michel; Haigron, Pascal; Avril, Stéphane
Abstract: Transcatheter aortic valve implantation is a recent mini‐invasive procedure to implant an aortic valve prosthesis. Prosthesis positioning in transcatheter aortic valve implantation appears as an important aspect for the success of the intervention. Accordingly, we developed a patient‐specific finite element framework to predict the insertion of the stiff guidewire, used to position the aortic valve. We simulated the guidewire insertion for 2 patients based on their pre‐operative CT scans. The model was designed to primarily predict the position and the angle of the guidewires in the aortic valve, and the results were successfully compared with intraoperative images. The present paper describes extensively the numerical model, which was solved by using the ANSYS software with an implicit resolution scheme, as well as the stabilization techniques which were used to overcome numerical instabilities. We performed sensitivity analysis on the properties of the guidewire (curvature angle, curvature radius, and stiffness) and the conditions of insertion (insertion force and orientation). We also explored the influence of the model parameters. The accuracy of the model was quantitatively evaluated as the distance and the angle difference between the simulated guidewires and the intraoperative ones. A good agreement was obtained between the model predictions and intraoperative views available for 2 patient cases. In conclusion, we showed that the shape of the guidewire in the aortic valve was mainly determined by the geometry of the patient's aorta and by the conditions of insertion (insertion force and orientation). Abstract : A new implicit finite element simulation framework was developed to predict the position of stiff guidewires during transcatheter aortic valve implantation. More specifically, we were able to accurately predict the angle and position of the guidewire at the aortic valve. The resolution was decomposed in 3 stages: initialization, free equilibrium, and final external operation (push or pull). A sensitivity analysis showed that insertion conditions have a higher influence on the final position than the guidewire mechanical properties. This highlights the interest of numerical simulations to assist clinicians in planning the optimal insertion conditions for a successful TAVI intervention.